Antioxidant and antibacterial potential of Malaysian Phyllanthus amarus thonn & schum, Phyllanthus niruri linn, and Phyllanthus urinaria linn - Tan, Poh Hwa (2012)
Natural products have long been consumed because of its convincing abilities in treating health related diseases. With the progression of science and technology, the use of natural products for medical applications is getting more popular and is being recognized. One of the most prominent traditional plant in Malaysia in which its medicinal values has yet to be discovered is Phyllanthus species. It originates from the family of Euphorbiaceae. This family comprises over 700 species in the world of flora and is well distributed mostly in tropical and subtropical countries. We often face the restriction to obtain health benefited medicinal plants continuously from wild. And, the bioactive activities from plants may vary from different location because of different biotic growth environment. Beside that, there is limited research study on health related properties about this plant in Malaysia especially the comparison among three different species. Thus, this study was conducted to determine the antioxidant and antibacterial activities of three Phyllanthus species and to identify possible polyphenols that are present in these plants. All plants were cultured at the same sheltered net house and growing condition. The supply of plants sources were continuous and standardized to minimize variation of active ingredient content which could occur as a result of environmental abiotic and biotic stress. The aerial section of Phyllanthus amarus, Phyllanthus niruri and Phyllanthus urinaria was extracted with methanol and water. Water extract antioxidant activity and total phenolic content decreased in the order of Phyllanthus niruri > Phyllanthus amarus > Phyllanthus urinaria. However, methanol extract showed that this activity decreased in the order of Phyllanthus niruri > Phyllanthus urinaria > Phyllanthus amarus. From a positive correlation of 0.954 < r2 < 1.000 between antioxidant activity and total phenolic content, methanol extract showed higher total phenolic content and antioxidant activity as compared with water extract. ANOVA test indicated a significant difference of antioxidant activity among the species in water and methanol extract. Water extract and methanol extract at the concentration of 100 mg/mL and 50 mg/mL of the three plant samples tested against both gram positive and gram negative bacterial. Both extract inhibited gram positive bacterial only at the range of inhibition zone of 1.15 to 1.70 cm. Lowest minimum inhibition concentration value for water extract and methanol extract were < 2.5 mg/mL and < 0.625 mg/mL. Value for minimum bactericidal concentration of water and methanol extracts were > 2.5 mg/mL and > 0.625 mg/mL.Polyphenol compounds, gallic acid, digalloyglucopyranoside, corilagin and geraniin were identified from water and methanol extract. Gallic acid was found in water extract of all three species only. Geraniin was found in both water and methanol extract of all three species as major compounds and highest concentration. Corilagin and digalloyglucopyranoside were only identified in water and methanol extract of Phyllanthus niruri. Overall, water extract yielded more types of phytochemicals. The study concluded that methanol extract showed higher and wider inhibition potential than water extract. Phyllanthus niruri possess the most potent protective and antioxidant activity among the species. Listeria monocytogenes and Staphylococcus aureus were the most sensitive strains.